Urban poverty and party populism in African democracies - Danielle Resnick, United Nations University, Helsinki (New York Cambridge University Press, 2014)
Urbanization, voting behavior, and party politics in African democracies -- Drivers of voting behavior among Africa's urban poor : why populist strategies prevail -- The bite of "King Cobra" : populist strategies in the Zambian context -- Gorgui's gamble : the rise and fall of populist strategies in Senegal -- The view from below : how the urban poor react to political party strategies -- Beyond the city : building coalitions with rural voters -- Political parties and populist strategies in other African democracies -- Conclusions, contributions, and implications.
Includes bibliographical references and index.
Keywords: Urban poor--Political activity--Africa.